THE ROLE OF ENGLISH GRAMMAR INSTRUCTION IN THE DEVELOPMENT OF CRITICAL THINKING SKILLS - Ergasheva Ozodabonu Bahodirjon qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article explores the relationship between English grammar instruction and the development of critical thinking skills among learners. While grammar teaching is often perceived as a mechanical aspect of language learning, this study highlights its cognitive potential in fostering higher-order thinking abilities. Through a review of theoretical frameworks and classroom practices, the research demonstrates how structured grammar instruction can stimulate analytical reasoning, syntactic awareness, and problem-solving capabilities. Recommendations for educators on integrating critical thinking into grammar lessons are also provided.